T-wave oversensing and symptomatic bradycardia in a pacemaker-dependent heart failure patient due to drug-induced hyperkalemia - Zekeriyeyev, Samuray; Canpolat, Uğur; Aytemir, Kudret (Acta Medica, 2023)
Hyperkalemia is a common clinical condition among heart failure patients especially if there is coexisting older age, potassium-sparing medication, and renal insufficiency. Close follow-up and titration of renin-angiotensin-aldosterone system inhibitors are essential to prevent the development of hyperkalemia. It can also cause significant abnormalities in patients with cardiac implantable electronic devices (CIED) including pacemakers and implantable cardioverter defibrillators (ICD) due to its impact on cardiac electrophysiology. Herein, we presented a pacemaker-dependent heart failure patient with single-chamber ICD in whom bradyarrhythmia signs and symptoms were observed due to T-wave oversensing and managed appropriately.